The Influence of Organizational Citizenship Behavior, Learning Organization and Transactional Leadership on Competence, Training Education (Diklat) and Employee Performance in the Youth Culture and Sports and Tourism Office of Surabaya City - Nurhayati, Dewi; Riyadi, Slamet; Sumiati, Sumiati (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
This study aims to analyze and prove the effect of Organizational Citizenship Behavior, Learning organization and Transactional Leadership on Competence, Training Education and Employee Performance at the Surabaya City Culture, Youth and Sports and Tourism Office.  In this study, the method used was a simple random sample.  Determination of the number of samples using the Slovin formula with a sample size of 60 people. The type of research conducted in this study is using explanatory research, namely research that explains the causes and effects of existing problems with the help of SEM PLS. The results of this study indicate that Organizational Citizenship Behavior has a positive but insignificant effect on employee performance at the Surabaya City Culture, Youth and Sports and Tourism Office. In contrast, Learning Organization behavior and Transactional Leadership both have a positive and significant effect on employee performance. Organizational Citizenship Behavior also has a positive and significant effect on employee competence, as well as Learning Organization and Transactional Leadership, both of which also have a positive and significant effect on employee competence. Meanwhile, Learning Organization has a positive and significant effect on education and training, but Transactional Leadership has no significant effect on education and training in the agency.